Karyotype variability in neotropical catfishes of the family pimelodidae (teleostei: Siluriformes) - Neto, Américo Moraes; Silva, M. R. da; Matoso, D. A.; Vicari, Marcelo Ricardo; Almeida, Mara Cristina de; Collares-Pereira, M. J.; Artoni, Roberto Ferreira (Neotropical Ichthyology, 2011)
Karyotypic data are presented for four species of fish belonging to the Pimelodidae family. These species show a conserved diploid number, 2n = 56 chromosomes, with different karyotypic formulae. The analyzed species showed little amount of heterochromatin located preferentially in the centromeric and telomeric regions of some chromosomes. The nucleolus organizer regions activity (Ag-NORs) and the chromosomal location of ribosomal genes by fluorescent in situ hybridization (FISH), with 18S and 5S probes, showing only one chromosome pair marked bearer of ribosomal genes, the only exception was Pimelodus britskii that presented multiple NORs and syntenic location of the 18S and 5S probes. Non-Robertsonian events, as pericentric inversion and NORs duplication are requested to explain the karyotype diversification in Pseudoplatystoma from the rio Paraguay (MS), Pimelodus from the rio Iguaçu (PR), Sorubim from the rio Paraguay (MS) and Steindachneridion from the rio Paraíba do Sul (SP). The obtained data for the karyotype macrostructure of these species corroborates a conserved pattern observed in Pimelodidae. On the other hand, interspecific variations detected by molecular cytogenetics markers made possible cytotaxonomic inferences and differentiation of the species here analyzed. © 2011 Sociedade Brasileira de Ictiologia.
Keywords: Pimelodidae; Pimelodus; Pseudoplatystoma; Robertsonia; Siluriformes; Sorubim; Sorubim Lima; Teleostei